Povezanost učnih ciljev z učiteljevo izbiro učne oblike - Plešec Gasparič, Romina; Valenčič Zuljan, Milena (Sodobni didaktični diskurzi v kontekstu pedagoške tradicije: Monografija v počastitev 80-letnice prof. dr. Martina Kramarja, 2025)
Learning forms held a central place in Kramar’s work (1990, 2009), as he identified them as a key didactic element that significantly contributes to the achievement of educational goals. This paper presents the results of a survey conducted with a sample of 422 Slovenian teachers, focusing on the relationship between educational objectives and the choice of teaching forms. The findings show that most teachers agree that learning objectives influence their selection of learning formats. Teachers who place a strong emphasis on developing critical thinking, fostering creativity, and promoting student collaboration are more likely to choose group learning formats than those who do not. Likewise, teachers who prioritize the development of student self-regulation are more inclined to use pair work. In interpreting the results, we engage in a dialogue with Kramar’s findings, particularly his emphasis on the relationships among students and between teachers and students, and how these relationships enhance the quality of instruction through the use of varied teaching forms.